Gambaran Hasil Pemeriksaan Tes Cepat Molekuler (TCM) pada Pasien Tuberkulosis Usia Produktif di Puskesmas Cibatu - Edi Suharto; Agus Sudrajat; Wulan Fitriani Agustin (Jurnal Infokes, 2023)
Tuberculosis (TB) is a disease related to the respiratory system caused by the bacterium Mycobacterium tuberculosis and is a global health problem, including in Indonesia. Early detection using rapid molecular testing (TCM) plays an important role in the diagnosis of TB. This study aims to describe the description of the results of the Molecular Rapid Test (TCM) examination in Pulmonary TB patients at the Cibatu Health Center for the period April - July 2023. This study was conducted at the Cibatu Health Center laboratory using descriptive methods, The subjects of this study were all data from the Tuberculosis Information System (SITB) and patient medical records at the Cibatu Health Center from April to July 2023. The majority of patients in this study showed negative MTB results (88.8%), sensitive MTB Rif (10.7%), resistant MTB Rif (0.4%). Based on the frequency distribution of gender, it can be concluded that the incidence of Pulmonary TB in TB patients at the Cibatu Health Center for the period April - July 2023 is more common in men than women.